IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH OLEH KEPALA SEKOLAH DITINJAU DARI MANAJEMEN KURIKULUM DAN MANAJEMEN KEUANGAN [IMPLEMENTATION OF SCHOOL BASED MANAGEMENT BY PRINCIPAL IN TERMS OF CURRICULUM MANAGEMENT AND FINANCIAL MANAGEMENT] - Rahajeng Marisya Nurfatin (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2021)
The principal has an important role in every stage of curriculum management and financial management, in this case it includes planning, implementing and monitoring evaluations. However, what about the role of the MBS model school principals in private schools in both curriculum management and financial management, and what factors influence the role of the principal in the Tangerang XYZ Kindergarten private school. The research method used is qualitative-case study. Data were obtained through semi-structured interviews, focus group discussions, observation studies, and documentation studies. While testing the validity of the data is used triangulation method. Based on the findings of the study it was concluded that there were restrictions on the authority of the principal, which had an impact on the role of the principal at each stage of management, especially curriculum management and financial management, with three factors influencing, namely (1) the dominance of the family foundation, (2) the status of the principal PNS and (3) lacking the attitude of the principal as a leader.